A Review Paper on Virtualization (International Journal of Innovative Research in Computer Science & Technology, 2022)
Virtualisation refers to the partitioning of  computer capabilities. A virtualized computational  atmosphere's purpose is to improve resource utilization by  presenting consumers and programs with a unified system  operational system based on a collection of homogenous  and unsupervised components. Virtualisation has recently  emerged as a technique of boosting data safety, reliability,  and durability, cutting prices, and configurability at all  layers (system, storage, and network). Clouds storage is a  layer of computation that exists beyond the equipment and  the systems software, and also the programs that execute  on front of it. The intermediary barrier that conceals the  material assets of the software systems from the operational  systems is known as the virtual machine monitor (VMM)  or hypervisor (OS). This page discusses the principles of  provides a platform, including its advantages and  disadvantages, taxonomy, and challenges.
Keywords: Computer; Machine; Operating System; VMM; Virtualization